(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In recent decades, the problem of oral mucosal leukoplakia has become increasingly relevant in light of the growing number of diagnosed cases of this disease. Leukoplakia, which is whitish spots or plaques on the mucous membrane that cannot be erased and do not correspond to any other clinical diagnosis, is one of the most common precancerous conditions of the oral cavity. Due to the potential ability of these changes to develop into an invasive cancer, the issues of effective treatment and prevention of leukoplakia occupy an important place in modern dentistry and oncology.